2019
DOI: 10.1021/acs.analchem.9b00264
|View full text |Cite
|
Sign up to set email alerts
|

Spectro-Mechanical Characterizations of Kerogen Heterogeneity and Mechanical Properties of Source Rocks at 6 nm Spatial Resolution

Abstract: In situmeasurements of the chemical compositions and mechanical properties of kerogen help understand the formation, transformation, and utilization of organic matter in oil shale source rocks. However, the optical diffraction limit prevents attainment of nanoscale resolution using conventional spectroscopy and microscopy. Here, we developed peak force infrared (PFIR) microscopy for multimodal characterization of kerogen in organic shales. PFIR microscopy provides correlative infrared imaging, mechanical mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 60 publications
3
46
0
Order By: Relevance
“…This suggests that an upper limit on the resolution of the TAP525 is set at 25 GPa kerogen. The different mean moduli between samples probably reflect chemical differences in OM, supported by observations by Jakob et al (2019) who showed that there is significant chemo-mechanical variation even within a single sample. The effects of OM chemistry on mechanical properties are still an open question (Li et al 2018b, a;Goodarzi 2018), although some preliminary work has been done by Emmanuel et al (2016), who suggest that increasing maturity causes stiffening in organic material.…”
Section: Organic Mattersupporting
confidence: 55%
See 2 more Smart Citations
“…This suggests that an upper limit on the resolution of the TAP525 is set at 25 GPa kerogen. The different mean moduli between samples probably reflect chemical differences in OM, supported by observations by Jakob et al (2019) who showed that there is significant chemo-mechanical variation even within a single sample. The effects of OM chemistry on mechanical properties are still an open question (Li et al 2018b, a;Goodarzi 2018), although some preliminary work has been done by Emmanuel et al (2016), who suggest that increasing maturity causes stiffening in organic material.…”
Section: Organic Mattersupporting
confidence: 55%
“…Such intra-sample variability therefore precludes inter-sample comparison unless the repeatability of AFM measurements can be demonstrated. The results of Jakob et al (2019) show that mechanical differences between OM in shales that are equally mature from the perspective of RockEval may still yield mechanical differences at the nanoscale that are the result of maturity-related heterogeneity. Therefore, demonstrating the repeatability of AFM results is crucial to interpret their mechanics reliably.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This method has been demonstrated on a variety of samples to provide spectroscopic imaging with a spatial resolution as high as 6 nm, as well as complimentary nano-mechanical information. [20,22] In this communication, we show that PFIR microscopy is a competitive imaging method for studying 2D polaritonic materials. PhPs of hexagonal boron nitride (h-BN) were revealed, and their dispersion relations were extracted, similar to studying h-BN by using the imaging capability of s-SNOM.…”
mentioning
confidence: 78%
“…PFIR microscopy operates in the peak force tapping mode that can avoid sample damage. This method has been demonstrated on a variety of samples to provide spectroscopic imaging with a spatial resolution as high as 6 nm, as well as complimentary nano‐mechanical information …”
mentioning
confidence: 99%